Kontruksi Budaya PATRIARKHI Bagi Perempuan di Indonesia dan India - Ummu Kulsum (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
This unique woman has always been the subject of discussion in all walks of life, with the theory of nurture and nature. The meaning of the